Reactions involving H, OH and O species on rhodium in H2SO4·12H2O and HClO4·5.5H2O in the range 198–298 K - Florit, María Inés (1995)
The voltammetric behaviour of polycrystalline rhodium in H2SO4·12H2O and HClO4·5.5H2O was investigated by conventional and triangularly modulated voltammetry in the range 198–298 K. H and OH electrosorption reactions and a fast electrochemical process in the potential range preceding the oxygen evolution reaction (OER) were studied. For both electrolytes, as the temperature diminished, the H atom reactions and those reactions related to the O-containing surface species became increasingly irreversible, whereas the fast electrochemical process preceding the OER was nearly the same, irrespective of the temperature. Explanations recently advanced for the behaviour of Rh in more diluted solutions of the same acids at 298 K and the electrochemical behaviour of the different processes are discussed, considering mainly the effects of sulphate anion adsorption and perchlorate anion decomposition on Rh.